A cat like that [book with audioplayer] - Laminack, Lester L., 1956- ([Library Ideas, LLC], 2025)
A sociable, big, round cat, saunters through town and visits the bakery, the bookstore, the pier, and the townsfolk all know her route and when she will reappear.